Analysis Of Overall Equipment Effectiveness (Oee) In Determining Productivity In Semi Automatic Semi Solid Filling Machines At PT X. - Dessi Lina Purnamasingrum; Ahmad Fuad Afdhal; Asal Asal (Jurnal EduHealth, 2023)
One of the manufacturing industries such as the cosmetics manufacturing industry still have tight and competitive competitiveness. The tight competition forces employers or management to continue to try to improve competitiveness. In the current era of globalization, so that the company can survive in competition, the company must be able to manage its resources such as humans, machines or other supporting facilities, as the conditions in question are ready to use to carry out its production operations, both accuracy, ability or its capacity. This study discusses the analysis of Overall Equipment Effectiveness (OEE) on a semi-automatic filling machine semi-solid at PT.X with the aim to provide input to the problems faced by the OEE calculation analysis and reveal the root cause of the problem. This study determines what efforts are made to increase the OEE value by using Fishbone, Failure Mode and Effect Analysis (FMEA) and how it is implemented. In this research, the results of the average calculation for July-September 2018 obtained availability values of 74.24%, performance rates of 54.53%, quality rates of 81.52% and OEE 30.56%. The value of Failure Mode and Effect Analysis (FMEA) obtained the highest value found in Equipment Failure Losses (RPN = 80), Defect losses (RPN = 64) and Idling and minor stoppage (RPN = 60). From the results of these losses found the root of the problem which causes the value of the percentage loss. The level of risk from the root cause of the performance of semi-solid semi-automatic filling machines is the standard replacement of unsuitable spare parts and no buffer stock. Lack of operator awareness and maintenance parts so autonomous maintenance must be improved again.